Densities of Foetal Clavicles during Second and Third Trimesters - Ghaus, Farah; Rahman, Nusra; tandon, Rati; Moinuddin, Arsalan; Akram, Waqar; Faruqi, Nafis Ahmad (Academia Anatomica International, 2017)
Background: Density of bone is directly affected by mineralization, which makes visualization by ultrasonography possible to follow foetal growth from early gestation to term. Clavicle being the first bone to ossify and the only bone to transmit upper limb weight to the axial skeleton, receives special attention by the scientists. Methods: Forty-nine foetal clavicles were divided into five groups. Statistically densities of the clavicles were measured and values between groups were compared. Results: Density was constant in all the groups and both in males and females. Conclusion: It was concluded that matrix formation in clavicles keeps pace with their mineralization during 2nd and 3rd trimesters.